2018
DOI: 10.1016/j.phrs.2018.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumor DNA – Current state of play and future perspectives

Abstract: Cancer management paradigms are shifting towards a personalized approach thanks to the advent of the -omics technologies. Liquid biopsies, consisting in the sampling of blood and other bodily fluids, are emerging as a valid alternative to circulating tumor biomarkers and tumor tissue biopsies for cancer diagnosis, routine monitoring and prognostication. The content of a liquid biopsy is referred to as the "tumor circulome". Among its components, circulating tumor DNA (ctDNA), including both cell-free and exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 99 publications
(115 reference statements)
0
30
0
Order By: Relevance
“…In human oncology, current studies focus on the analysis of DNA released from tumor cells in plasma (ctDNA), which is much more cancer-specific. Today one ctDNA assay for the detection of EGFR mutation in patients with non-small cell lung cancer (NSCLC ) has been approved by the Food and Drug Administration, and ctDNA assays for EGFR in NSCLC and KRAS in colorectal cancer are available for commercial use in Europe 3,4,54 . As in human, ctDNA has also been found in some canine cancers such as lymphoma 20 , mammary carcinoma 50 and more recently in pulmonary adenocarcinoma 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human oncology, current studies focus on the analysis of DNA released from tumor cells in plasma (ctDNA), which is much more cancer-specific. Today one ctDNA assay for the detection of EGFR mutation in patients with non-small cell lung cancer (NSCLC ) has been approved by the Food and Drug Administration, and ctDNA assays for EGFR in NSCLC and KRAS in colorectal cancer are available for commercial use in Europe 3,4,54 . As in human, ctDNA has also been found in some canine cancers such as lymphoma 20 , mammary carcinoma 50 and more recently in pulmonary adenocarcinoma 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free DNA (cfDNA) circulates in plasma and other body fluids such as urine, cerebrospinal fluid, pleural fluid and saliva as short double-stranded DNA fragments of about 160 base pairs. In healthy patients, cfDNA is released during cell deaths like apoptosis or necrosis, or by active secretion, and comes mainly from the hematopoietic lineage with minimal contributions from other tissues [1][2][3][4] . Since its first discovery in human in 1948 5 , it was shown that cfDNA in the blood reflects various pathological processes such as inflammatory disease, sepsis, trauma, stroke and cancer, and its concentration is correlated with disease severity and prognosis 2,[6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Determining tumor proliferation and metastases in CTCs are performed using DNA methylation [ 162 ]. Furthermore, ctDNA technologies provide a series of analyses including single gene mutational evaluation, next generation deep genome sequencing, following analysis of methylation, where their application covers all stages of cancer management [ 163 ].…”
Section: Identifying Os Stem Cell Populations As Therapeutic Targetsmentioning
confidence: 99%
“…Its sensitivity for early detection can be limited by low amount of ctDNA because of low tumor burden, leading to 0.02% MAF sensitivity. A number of advanced technologies can facilitate methods required for enhancement of the sensitivity including unique molecular identifiers (UMIs) in the amplification step preceding sequencing and the in vitro and in silico improvement of ctDNA using virtue of shorter fragment length of them [ 163 ].…”
Section: Identifying Os Stem Cell Populations As Therapeutic Targetsmentioning
confidence: 99%
“…Analysis of circulating tumor DNA (ctDNA) can be used to identify therapeutically actionable mutations, monitor disease progression, detect residual disease and track the genomic evolution of treatment resistance [1][2][3][4]. The genomic profiling of ctDNA using whole genome, whole exome or targeted sequencing is feasible, but technically challenging due to the low quantities and fragmented nature of ctDNA [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%